Shattered in real life [videorecording (DVD)] - Woods, Justin; Durbin, Chris Todd (Filmhub, 2026)
Shattered in Real Life is a powerful documentary exploring the profound impact of drunk and distracted driving on individuals and communities. Through compelling interviews with real people who have both suffered from and caused accidents.